RANCANG BANGUN APLIKASI GIS PUSAT OLEH OLEH KOTA PADANG DENGAN AR BERBASIS ANDROID - Ferdian Rayata; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Padang is the largest city in the province of West Sumatra. The city is known as a tourist town. In addition, the city is included in the strategic town traffic lane Sumatra. Many migrants are interested in visiting this city. In addition to many tourist objects there are facilities that support from the tourism such as: souvenir. However, lying scattered in various areas of the city of Padang, Make information on the attractions are still hard to come by public although migrants who visit this city.The development of communication technology which is currently developing an outstanding effect. Android based smartphone communication tools more and more popular every person in search of information about the existence of the location and the address of a place that is difficult to find when needed. To overcome this problem, the authors aim to design locator application padang souvenir with location-based services  ( LBS ). By displaying a digital map using google maps features and augmented reality. Applications designed using Android development Tool, mixar, augmented reality browser, And editor Eclipse integrated development environment (IDE). While the programming language used is Java , extensible languange , hypertext preprocessor (PHP) and query structure languange (SQL).This application helps users find out information on attractions such as distance , direction , address that appears in the form of digital maps. Not only that, through augmented reality technology is pasted on android smartphone, Users can interact with the real world through the camera view to locate the attractions that are nearbyKeyword : tourism, location based service, augmented reality, android